Hypoxia-Inducible Factor 1α and 2α Have Beneficial Effects in Remote Ischemic Preconditioning Against Stroke by Modulating Inflammatory Responses in Aged Rats - Du, Xiangnan; Yang, Jian; Liu, Cuiying; Wang, Sainan; Zhang, Chencheng; Zhao, Heng; Du, Huishan; Geng, Xiaokun (Frontiers in Aging Neuroscience, 2020)
Limb remote ischemic preconditioning (RIPC) has been proven to alleviate stroke injury in young rats, but its protective effect and its mechanism in aged rats are still unclear. Hypoxia-inducible factor (HIF) is one of the important markers of stroke, and its high expression plays an important role in the pathogenesis of stroke. In this study, we tested the hypothesis that RIPC could regulate the expression of HIF, leading to reduced inflammatory responses in aged rats. Stroke was induced by transient middle cerebral artery occlusion (MCAo) in aged rats, and RIPC was conducted in both hind limbs. The HIF-1 and HIF-2 mRNA and protein were examined by real-time RT-PCR and western blotting (WB). Inflammatory cytokines in the peripheral blood and brain were measured using AimPlex multiplex immunoassays. The protein levels of p-Akt, Akt, p-ERK and ERK were examined by WB. We investigated that RIPC reduced the infarct size, improved neurological functions, and decreased the expression of HIF-1 and HIF-2 in the ischemic brain. RIPC reduced the levels of IL-1, IL-6 and IFN- in the peripheral blood and the levels of IL-1 and IFN- in the ischemic brain 48 h post-stroke. Moreover, intraperitoneal injection of the HIF inhibitor, acriflavine hydrochloride (ACF), abolished the protection of RIPC with respect to infarct size and neurological functions and neutralized the downregulation of pro-inflammatory IL-1, IL-6 and IFN-. ACF also reversed the activation of the Akt signaling pathway induced by RIPC following stroke. HIF may play a key role in RIPC, which was likely mediated by the Akt signaling pathway and systemic modulation of the inflammatory response.